Characterization and screening of cyclooxygenase-2 inhibitors from Zi-shen pill by affinity ultrafiltration-ultra performance liquid chromatography mass spectrometry. (15th September 2019) - Huai, Jiaxin; Zhao, Xiaoning; Wang, Siqi; Xie, Linlin; Li, Yiran; Zhang, Teng; Cheng, Congcong; Dai, Ronghua
Abstract: Ethnopharmacological relevance: Zi-shen pill (ZSP) is a classical Chinese herbal formula used for treatment of benign prostatic hyperplasia (BPH). Aim of the study: To characterize and screen cyclooxygenase-2 (COX-2) inhibitors from ZSP extract. Materials and methods: The ZSP extract was incubated with COX-2 and the potential ligands were screened out by affinity ultrafiltration. Celecoxib and glipizide were chosen as positive control and negative control drug, respectively. Affinity ultrafiltration-ultra performance liquid chromatography-mass spectrometry (UPLC-MS) method was used. In addition, in vitro COX-2 inhibitory assay and in silico molecular docking technique were used for further validation. Results: A total of 20 components were discovered and identified from ZSP ultrafiltrate by high resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS), among which 8 compounds were deduced as potential COX-2 inhibitors by their high specific binding values (>1.5). Inhibitory activities of demethyleneberberine, palmatine, berberine and timosaponin A-I were confirmed by an enzyme assay of COX-2, which validated the reliability of our approach. Molecular docking simulation investigated potential mechanism of action for these compounds. Conclusion: The results revealed that affinity ultrafiltration UPLC-MS could successfully screen out the potential COX-2 inhibitors from complex Chinese herbal formula ZSP extract, indicating that its therapeutic effect on BPH was partly based on the enzyme active ingredients.